Jilbab dalam Pandangan Muhammad Sa'id al-'Asmawi - Safala, Udin; Makmun, Rodli (IAIN Ponorogo, 2013)
Abstract: Discussing the headscarf as a dress model in Islam is truely like talking about an outdated case because so many academics both from the West and the Islamic world itself has discussed it before. Yet, when confronted with the theoretical framework and approach or contemporary perspective, probably there is still academic space that can be used as a basis of analysis of long debate related to the jilbab, khima>r, muqna’, or clothing that are believed having value of shar’i> (Islamic laws). This paper attempts to explore, within its limitations, the concept of the veil/ headscarf through the thinking of Muhammad Sa’i> d al-’Asthma> wi> which are categorized by Wael B. Halla>q as a person in the area of liberal Islam. Through the theoretical framework of law, by using the historical approach of assets of jurisprudence ( usu>l al-fiqh), al-’Asthma> wi>, the writer tries to position the concept of veil in Islamic teaching which is different from other islamic thinkers.